Are physical activity levels of health care professionals consistent with activity guidelines? A prospective cohort study in New Zealand. (February 2018) - Chan, Lydia; McNaughton, Harry; Weatherall, Mark
Objective: We aimed to estimate the level of physical activity undertaken by health care professionals and the proportion that achieved a daily target of 10, 000 steps. Design: This was a prospective cohort study. Setting: Participants were recruited in Wellington Regional Hospital, a tertiary hospital in New Zealand. Participants: Neurology, Cardiology, and Endocrinology staff were invited to participate. Main outcome measures: Pedometer-measured step counts were recorded over seven days and the proportion that achieved a daily target of 10, 000 steps was calculated. Results: We included 50 staff in the study. The mean daily step count was 10, 620 (standard deviation = 3141) with a median daily step count of 10, 606 (interquartile range = 7791–12, 469). Sixty-five per cent of the staff achieved 10, 000 steps per day. Conclusion: This cohort was more active compared to other pedometer-based studies in health care professionals. The daily target of 10, 000 steps per day was achieved at a higher proportion than reported in international studies and the general New Zealand.